The Effect of Groundstroke Forehand Exercise on Speed and Agility in 14 to 16-year-old Tennis Athletes - Rices Jatra; Alnedral Alnedral; Kamal Firdaus; Nagoor Meera Abdullah; Alexandre Sibomana (CV. FOUNDAE, 2024)
This research addresses gaps by developing a holistic training model that integrates essential elements for optimal tennis performance. The study explores how physical conditioning can enhance agility, speed, and overall performance of junior athletes aged 14 to 16, focusing on forehand drive. The aim is to provide insights for coaches and players by integrating physical and technical training to improve performance. The scope includes evaluating the effectiveness of a forehand drive training program supplemented with speed and agility exercises for junior tennis players. An experimental one-group pre-test-post-test design was employed. Eleven tennis athletes from the Nusalima Tennis Academy participated. Speed was measured using a 20-meter sprint, and agility was calculated using the 505 Agility Test. The training program spanned 12 sessions over four weeks. Statistical analysis included mean, standard deviation, normality tests, and t-tests. Pre-test and post-test results showed significant improvements in speed and agility. The t-test values indicated statistical significance, confirming the effectiveness of the forehand drive training model. Players demonstrated enhanced neuromuscular adaptation, muscle strength, coordination, and reaction time. The study concludes that the forehand drive training model significantly improves speed and agility in junior tennis players. The findings support the theory that focused and structured training enhances physical abilities and performance. Additionally, the research highlights the long-term health benefits of intensive tennis training, such as improved cardiovascular health and overall fitness. The training model can be widely applied to develop well-rounded athletes in tennis programs.